MODEL PROBLEM BASED LEARNING BERBANTUAN CISCO PACKET TRACER UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF DAN KETERAMPILAN LITERASI DIGITAL SISWA DI SMKN 9 BENGKULU UTARA - Andika, Caca; Hidayat, Tomi; Fitriani, Apriza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the differences in the effects of the Problem-Based Learning model assisted by Cisco Packet Tracer (PBL-CPT), Problem-Based Learning (PBL), and conventional learning on students’ cognitive learning outcomes and digital literacy skills at SMK Negeri 9 Bengkulu Utara. This research employed a quasi-experimental method using a pre-test and post-test control group design. The sample consisted of three tenth-grade classes, including two experimental classes that applied the Problem-Based Learning model assisted by Cisco Packet Tracer (PBL-CPT) and the Problem-Based Learning (PBL) model, as well as one control class that used the conventional learning model. Data collection was conducted using multiple-choice and essay tests to measure cognitive learning outcomes, and questionnaires to assess students’ digital literacy skills. The data were analyzed using the One-Way ANOVA test. The results showed that there were significant differences in cognitive learning outcomes and digital literacy skills among students taught using the Problem-Based Learning model assisted by Cisco Packet Tracer (PBL-CPT), the Problem-Based Learning (PBL) model, and the conventional learning model. Furthermore, the Problem-Based Learning model assisted by Cisco Packet Tracer (PBL-CPT) was found to be more effective in improving students’ cognitive learning outcomes and digital literacy skills.